Influence of patch size and chemistry on the catalytic activity of patchy hybrid nonwovens. Issue 1 (12th December 2019) - Hils, Christian; Dulle, Martin; Sitaru, Gabriel; Gekle, Stephan; Schöbel, Judith; Frank, Andreas; Drechsler, Markus; Greiner, Andreas; Schmalz, Holger
Abstract : In this work, we provide a systematic kinetic study on the influence of the patchy structure of electrospun hybrid nonwovens on their catalytic activity in the gold nanoparticle (Au NP)-catalysed alcoholysis of dimethylphenylsilane in n -butanol. Abstract : In this work, we provide a detailed study on the influence of patch size and chemistry on the catalytic activity of patchy hybrid nonwovens in the gold nanoparticle (Au NP) catalysed alcoholysis of dimethylphenylsilane in n -butanol. The nonwovens were produced by coaxial electrospinning, employing a polystyrene solution as the core and a dispersion of spherical or worm-like patchy micelles with functional, amino group-bearing patches (dimethyl and diisopropyl amino groups as anchor groups for Au NP) as the shell. Subsequent loading by dipping into a dispersion of preformed Au NPs yields the patchy hybrid nonwovens. In terms of NP stabilization, i.e., preventing agglomeration, worm-like micelles with poly( N, N -dimethylaminoethyl methacrylamide) (PDMA) patches are most efficient. Kinetic studies employing an extended 1 st order kinetics model, which includes the observed induction periods, revealed a strong dependence on the accessibility of the Au NPs' surface to the reactants. The accessibility is controlled by the swellability of the functional patches in n -butanol, which depends on both patch chemistry and size. As a result, significantly longer induction ( t ind ) and reaction ( t R ) times were observed for the 1 st catalysis cycles in comparison to the 10 th cycles and nonwovens with more polar PDMA patches show a significantly lower t R in the 1 st catalysis cycle. Thus, the unique patchy surface structure allows tailoring the properties of this " tea-bag "-like catalyst system in terms of NP stabilization and catalytic performance, which resulted in a significant reduction of t R to about 4 h for an optimized system.